2006
DOI: 10.1301/nr.2006.dec.518-531
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Monetary Incentives in Modifying Dietary Behavior: A Review of Randomized, Controlled Trials

Abstract: To review research evidence on the effectiveness of monetary incentives in modifying dietary behavior, we conducted a systematic review of randomized, controlled trials (RCTs) identified from electronic bibliographic databases and reference lists of retrieved relevant articles. Studies eligible for inclusion met the following criteria: RCT comparing a form of monetary incentive with a comparative intervention or control; incentives were a central component of the study intervention and their effect was able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 18 publications
0
54
0
2
Order By: Relevance
“…A nutrition study testing the effect of food provision to predominantly White, well-educated men and women recruited through newspaper advertisements, with and without a cash payment contingent on weight loss, found that differences among intervention groups were small, but favored groups with free food provision; however, this effect did not persist at 30 months. All treatment groups gained weight gradually after 6 months, with a convergence in mean weight loss toward the control group once formal treatment was withdrawn at 18 months (Glenny et al, 1997;Goodman & Anise 2006;NHS Centre for Reviews and Dissemination, 1997;Wall, Mhurchu, Blakely, Rodgers, & Wilton, 2006). A similar finding was reported where incentives included free food or cost sharing of food.…”
Section: -1999mentioning
confidence: 56%
“…A nutrition study testing the effect of food provision to predominantly White, well-educated men and women recruited through newspaper advertisements, with and without a cash payment contingent on weight loss, found that differences among intervention groups were small, but favored groups with free food provision; however, this effect did not persist at 30 months. All treatment groups gained weight gradually after 6 months, with a convergence in mean weight loss toward the control group once formal treatment was withdrawn at 18 months (Glenny et al, 1997;Goodman & Anise 2006;NHS Centre for Reviews and Dissemination, 1997;Wall, Mhurchu, Blakely, Rodgers, & Wilton, 2006). A similar finding was reported where incentives included free food or cost sharing of food.…”
Section: -1999mentioning
confidence: 56%
“…The incentives constituted the second highest cost for the entire Weight-Wise intervention (26% of total). However, previous research suggests that incentives have a positive effect on weight loss (Wall et al, 2006) and could be an important component for weight loss success. The personnel costs associated with the group sessions ($5308) comprised 31% of total costs.…”
Section: Discussionmentioning
confidence: 98%
“…Previous systematic reviews of the effectiveness of financial incentives to enhance weight loss have limited their scope to randomized controlled trials (RCTs) in the academic literature (6,13,23,24). Most reviews base their findings on less than 10 included studies, each of these studies with relatively small sample sizes (6,23,24). These reviews have found generally positive but mixed results with respect to weight loss.…”
Section: Introductionmentioning
confidence: 99%